Socioeconomic deprivation and inpatient complication rates following mastectomy and breast reconstruction surgery. Issue 9 (15th June 2015) - Jeevan, R.; Browne, J. P.; Pereira, J.; Caddy, C. M.; Sheppard, C.; van der Meulen, J. H. P.; Cromwell, D. A.
<x xml:space="preserve">Abstract</x> Background Socioeconomic deprivation is known to influence the presentation of patients with breast cancer and their subsequent treatments, but its relationship with surgical outcomes has not been investigated. A national prospective cohort study was undertaken to examine the effect of deprivation on the outcomes of mastectomy with or without immediate breast reconstruction. Methods Data were collected on patient case mix, operative procedures and inpatient complications following mastectomy with or without immediate breast reconstruction in the English National Health Service between 1 January 2008 and 31 March 2009. Multivariable logistic regression was used to examine the relationship between patients' level of (regional) deprivation and the likelihood of local (mastectomy site, flap, flap donor and implant) and distant or systemic complications, after adjusting for potential confounding factors. Results Of 13 689 patients who had a mastectomy, 2849 (20·8 per cent) underwent immediate reconstruction. In total, 1819 women (13·3 per cent) experienced inpatient complications. The proportion with complications increased from 11·2 per cent among the least deprived quintile (Q1) to 16·1 per cent in the most deprived (Q5). Complication rates were higher among smokers, the obese and those with poorer performance status, but were not affected by age, tumour type or Nottingham Prognostic Index. Adjustment for patient‐related factors only marginally reduced the association between deprivation and complication incidence, to 11·4 per cent in Q1 and 15·4 per cent in Q5. Further adjustment for length of hospital stay, hospital case volume and immediate reconstruction rate had minimal effect. Conclusion Rates of postoperative complications after mastectomy and breast reconstruction surgery were higher among women from more deprived backgrounds.